Selective secondary school education in Barbados: The need for change - Pilgrim, Marcia; Hornby, Garry; Inniss, Tara (My University, 2018)
This article examines the implications of selective secondary school education in Barbados for the provision of an inclusive and equitable education system and highlights its impact on educational outcomes. The concepts of inclusion and equity in education are discussed and their importance in achieving the education goals of nations within the English- speaking Caribbean are highlighted. The historical development of the selective secondary school system in Barbados is outlined and the inequity perpetuated by high stakes selection examinations are examined. The ongoing effects of the ability grouping that result from this process are discussed. The need for a move away from a selective secondary education system is proposed and a possible means for bringing about this change in Barbados is explored. This has important implications for countries in the Caribbean and in other parts of the world that have selective secondary school education systems.
Journal of International and Comparative Education, 2018, Volume 7, Issue 2
Keywords: equity; inclusion; selective education; ability grouping; education systems